Recent Advancements in Triazole-based Click Chemistry in Cancer Drug Discovery and Development - Kumar, Arun; Yadav, Ashok Kumar; Mishra, Vivek; Kumar, Deepak (SynOpen, 2023)
Triazole-based compounds possess a broad range of activity and can be synthesized using click chemistry. Many new chemotherapeutic agents have been developed in recent years by exploiting click chemistry and these are covered in this review.
Keywords: click chemistry; cycloaddition; triazoles; cancer; chemotherapy